Intelligent essential oil extraction system / Zakiah Mohd Yusoff ... [et al.] - Mohd Yusoff, Zakiah; Khirul Ashar, Nur Dalila; Razali, Noor Fadzilah; Muhammad, Zuraida; Zainal Abidin, Amar Faiz (Universiti Teknologi MARA, Kedah, 2019)
This product offers the popular steam distillation in a single unit. The product design is tailored to suite domestic and household applications. It comes in a counter top easy-to-use unit, with a compact and presentable look. The efficiency is promising and it even conserves more energy as compared to its industrial counterparts. With selectable dual-mode distillation, the product covers BROAD SPECTRUM OF RAW MATERIALS to be extract such as serai wangi, pandan, ginger, lemon and kaffir lime. Targetted at LOW-INCOME COMMUNITY or even cottage industries, this system is designed and developed with MINIMAL COST and attached with ROBUST CONTROLLER.The parts are easily replaceable with standards components available in the market. This effort might be indirectly help us to preserve and promote Malaysia invaluable herbs golobally. This plant is important since it offer a new technique to extract the essential oil where the thermal degradation problem of yield can be resolve. It also give a solution to small medium industries to generate income from essential oil extraction. This plant able to reduce the extraction time with intelligent and can contribute to less power consumption. The next project plan is to provide service and expertise in essential oil extraction and controller development. This project also have collaboration with other university which is Universiti Teknikal Melaka (UTEM), UiTM Pulau Pinang and one from the industry, Ikhlas Rasmi Sdn.Bhd. For the next future plan, this project will lead to other project which is we use induction based system as a source.